Development process and testing of partial discharge detection device on medium voltage XLPE cable - Mohamad Radzi M.I.F.; Ali N.H.N.; Mohd Ariffin A.; Abd Rahman M.S.; Rameli N.; Ahmad M.R.; Mohd Salleh A.S. (Institute of Advanced Engineering and Science, 2023)
High voltage assets play a vital role in providing uninterrupted power to the consumers and any slight problems experienced by the assets may cause losses in millions of dollars to businesses. Therefore it is of utmost importance to monitor the health of high voltage assets. This research presents the development process of a Partial Discharge (PD) device that is able to detect PD acoustic waves for monitoring high voltage assets purposes. Medium voltage Cross-Linked Polyethylene (XLPE) cable was used which was introduced with spherical void defects at the joints of the cable that functioned to produce PD acoustic waves. Outcome of the development processes provides the finished design of the PD sensing device, known as Partial Discharge Detection (PDD) device. The functionality of the PDD device was also assessed through controlled experimentations, and they proved to be successful. Pure PD waveform captured by the ultrasonic sensor was similar when compared to a HFCT sensor's pure PD waveform. The PDD device is a small and affordable, and is opened to various improvements such as integrating Artificial Intelligence (AI) unto the device, and one day may replace most existing bulky and expensive PD sensing devices that are readily available in the market. Copyright 2020 Institute of Advanced Engineering and Science. All rights reserved.